The Influence of Job Satisfaction, Organizational Commitment, and Knowledge Management on Employee Performance of PT Triesindo Mandiri Teknik - Jamila, Siti Hazizah; Esthi, Raniasari Bimanti Esthi (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Employees are one of the most critical assets of any organization. Productive and efficient employees are the key to business success. Employee performance is an essential factor in the success and sustainability of PT Triesindo Mandiri Teknik's business operations. Therefore, it is crucial to understand the influence of certain factors on employee performance. This study uses a type of quantitative research using non-probability sampling techniques with saturated sampling techniques; the sample size of this study is the entire population (a case study of PT Triesindo mandiri teknik production division totaling 90 employees). Data testing techniques used in this study include a validation test with factor analysis and a reliability test with Cronbach's alpha. Classical assumption test (normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t-test to test and prove the research hypothesis, and the coefficient of determination). (1) Job satisfaction has a positive relationship and affects employee performance, which is shown by the value of t count> t table or 2.950> 1.665 while the significance level> significance level or 0.004> 0.05 (2) Organizational commitment has a positive relationship and has an effect on employee performance, which is showing by the value of t count> t table or 3.031> 1, 665 while the significance level> significance level or 0.003> 0.05 (3) Management knowledge has a negative relationship and has an effect on employee performance designated with the value of t count> t table or -3.425> 1.665 while the significance level> significance level or 0.001> 0.05 (4) The results of the analysis of the three variables, namely job satisfaction, organizational commitment and management knowledge partially affect employee performance